History of the Detective Genre: A. C. Doyle's Series about Sherlock Holmes - MELIKHOV, Alexey Germanovich; NESMELOVA, Olga Olegovna; BRONICH, Marina Karpovna (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT This paper analyzes the relation of the series of works by Arthur Conan Doyle about Sherlock Holmes to the genre movement of the 1920-1930s called The Golden Age of detective fiction is not widely studied in the Russian literature analysis. As a result of this study, the author concludes that Doyle's series in all its differences from the representatives of the Golden Age of detective fiction laid out the conceptual framework of this genre movement. Stories about Sherlock Holmes if not invented, popularized many typical genre elements that were later actively used by the authors of detective works.RESUMEN Este artículo analiza la relación de la serie de obras de Arthur Conan Doyle sobre Sherlock Holmes con el movimiento de género de la década de 1920-1930 llamada “La Edad de Oro de la ficción detectivesca” es poco estudiado en el análisis de la literatura rusa. Como resultado de este estudio, el autor concluye que la serie de Doyle, en todas sus diferencias con los representantes de la Edad de Oro de la ficción detectivesca, estableció el marco conceptual de este movimiento de género. Las historias sobre Sherlock Holmes, si no se inventaron, popularizaron muchos elementos de género típicos que luego fueron utilizados activamente por los autores de los trabajos de detectives.